Crouzon’s Syndrome: tooth morphological and microanalytical evaluation - Pawlicki, R.; Knychalska-Karwan, Z.; Darczuk, D.; Nowak, T. (European archives of paediatric dentistry, 2008)
Aim : To assess the morphological and microanalytical structure of teeth in Crouzon’s Syndrome. Mthods : A 21 year-old patient with this condition was evaluated to demonstrate tooth morphology in this syndrome. Assessment of 4 teeth from this patient consisted of morphological analysis in SEM as well as microanalysis of elements. Sections were created in order to assess any defects of the enamel, dentine, root, and any demineralisation. Results : Micro-analysis using x-ray techniques revealed lower levels of calcium and magnesium from this patient with Crouzon’s as compared with samples from a normal healthy patient of comparable age. Furthermore, in the subject’s teeth notable amounts of lead were found. Conclusion : Histological images revealed morphological abnormalities especially in dentine. Furthermore, in the dentine levels of calcium and magnesium were lowered according to the microanalytical tests.